Summit between West Chester University, Pennsylvania, USA and Universidad Nacional, Heredia Costa Rica. Global Library Literacy Initiative: An Intercultural Learning Experience - Reyes, Awilda (2011)
This document describes the experience of academic cooperation between professionals in the field of library science, both from West Chester University (WCU), and the National University (UNA) of Costa Rica. The event took place at West Chester University during the week May 4th to May 8th, 2009. The objectives of this revolved around the exchange of ideas and interests in the academic and cultural relations between the two universities. In addition, it unveiled several services and procedures in the handling of information and highlighted the importance of promoting the exchange of students from both institutions. Finally, this article highlights the schedule of activities to integrate international and intercultural perspective in various areas related to the teaching-learning process, the contribution of university libraries on student success and techniques of information dissemination.